PEMBINAAN KEMANDIRIAN SOSIAL PADA ANAK USIA 4-5 TAHUN DI TK CAHAYA BERSERI PONTIANAK TIMUR - Khairunnisa, Khairunnisa; Mering, Aloysius; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIndependent is the desire or desire to do things for himself without the help of others. In independence is divided into five aspects of independence, namely social and emotional independence, physical independence and body functions, intellectual independence, self-reliance to use the environment to learn, and make decisions and choices. The purpose of this research is to find out information and describe social self-reliance development in 4-5 years old children in TK Cahaya Berseri Pontianak Timur. The method used is qualitative naturalistic method. The sample of the research is one teacher and 17 students. After the data collected, the presentation of data and then drawn a conclusion. The results of the study illustrate that the factors that cause the child is not independent in social aspects is the external factors of parenting parents who use the pattern of overprotection care and parenting patterns of the teacher is using permissive parenting patterns because teachers are less attention to children at the time in the classroom or outside of the classroom. As for the obstacles in fostering social independence of children is the parents yng less familiarize their children to hang out with friends and share with friends and share with friends. Planning activities that are less varied and less attractive for children.Keywords: Independent, development